The conundrum of conservation agriculture and livelihoods in Southern Africa - Nkala, P; Mango, Nelson; Corbeels, Marc; Jan Veldwisch, G; Huising, Jeroen (Academic Journals, 2011)
Low crop productivity, food insecurity, hunger and malnutrition; inadequate farming knowledge and skills, implements and inputs are characteristic of smallholder agriculture in Southern Africa. Many researchers argue that conservation agriculture can guarantee higher crop productivity, food security, improved livelihoods and environmental protection, better than the unsustainable traditional systems of slash and burn practices. In this paper, we present the results of a meta-analysis of over 40 academic publications to review conservation agriculture s role in influencing desired livelihood outcomes in Southern Africa. We conclude that the effectiveness of conservation agriculture towards better livelihood outcomes in Southern Africa remains debatable, especially when supportive government policies are lacking.